The concept of panigo in rural and urban areas of Leyte - Tomandao, Xenia Mae B. (Tacloban City Xenia Mae B. Tomandao, 1998)
The study was composed of four "paratigos" who were asked by the researcher to relate on how they learn to practice their craft of "panigo". There were also ten randomly interviewed respondents to get their views regarding the concept. The purpose of this is to determine whether the traditional belief of "panigo" of the ancient Filipinos still exists in this present society, may it be in the rural or urban areas of Leyte. The result of the study shows that despite the demand to be globally competent, the old rituals and practices regarding "panigo" remain to exist. It was hypothesized by the researcher that the "paratigo" engage in the practice of "panigo" to meet the demand of their economic needs. Results have shown that the practice of "panigo" is not a major source of their income. It does contribute but not to the extent of expanding the monthly income that they have. Thus, money is not their motivator to practice "panigo" but it is the fulfillment to be able to help people through this extraordinary process.
Keywords: "Panigo".; Social science